Sea Ice Loss and Arctic Cyclone Activity from 1979 to 2014 - Koyama, T; Stroeve, J; Cassano, J; Crawford, A (AMER METEOROLOGICAL SOC, 2017)
Extensive summer sea ice loss has occurred within the Beaufort, Chukchi, East Siberian, and Laptev Seas over the last decade. Associated anomalies in sensible and latent heat fluxes in autumn have increased Arctic atmospheric precipitable water and air temperatures, with the potential to impact autumn and winter cyclone activity. To examine if a connection exists between recent Arctic sea ice loss and cyclone activity, several cyclone metrics from 60° to 90°N are analyzed. Results show that following years with less September sea ice, there is a subsequent increase in moisture availability, regional baroclinicity, and changes in vertical stability that favor cyclogenesis. However, tracking of individual cyclones indicates no coherent increase in cyclone frequency or intensity associated with sea ice loss. Furthermore, no robust northward progression of extreme cyclones is observed.